2008
DOI: 10.1007/s00244-008-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Biomarkers Approach in Different Organs of Anodonta cygnea from the Dnister Basin (Ukraine)

Abstract: The aim of this study was to compare environmental quality in two sites in western Ukraine-rural (R) and urbanized (U)-with the usage of the resident bivalve mollusk Anodonta cygnea. The study was realized during three seasons. The metal uptake and a set of biochemical markers were determined. For each season, Cd and metallothioneins (MTs) contents in the digestive gland and gills of the mollusc were higher at the U site, reflecting its chronic pollution. The oxidative stress in the mollusk was observed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Besides that, the ratio of Cd in the composition of MTs was very low. The elevated level of Cd in the mussels and their MTs in this area was shown previously, despite other markers characterizing this area as a reference site (Falfushynska et al, 2009). MTs are able to accumulate metals from the environment with particular sensitivity for Cd (Hamza-Chaffai et al, 2000;Amiard et al, 2006).…”
Section: A B C D E F Gsupporting
confidence: 51%
See 2 more Smart Citations
“…Besides that, the ratio of Cd in the composition of MTs was very low. The elevated level of Cd in the mussels and their MTs in this area was shown previously, despite other markers characterizing this area as a reference site (Falfushynska et al, 2009). MTs are able to accumulate metals from the environment with particular sensitivity for Cd (Hamza-Chaffai et al, 2000;Amiard et al, 2006).…”
Section: A B C D E F Gsupporting
confidence: 51%
“…The variability of several biochemical and morphological indices between the groups and seasons without distinct regularity could complicate the assessment of the health status in the feral animals from these areas (Falfushynska et al, 2009(Falfushynska et al, , 2010(Falfushynska et al, , 2012. The high variability of the oxidative stress indices values, and their dependence more on the season than on the site (for GSH and TBARS, Mn-SOD and Cu,Zn-SOD), indicates this in the present study.Therefore, the assessment of several biomarkers is the most relevant way to evaluate the toxicity in the environment (Hagger et al, 2006;Cravo et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In previous studies on Anodonta sp., MT levels in the digestive gland have been shown to be a suitable marker of the environmental pollution (Falfushynska et al, 2009), and a significant induction of MTs was observed after 7 days of exposure to 80 μg Cu/L in Crassostrea virginica (Ringwood et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Other markers of specific kinds of pollution include cholinesterase activity (ChE, marker of pollution by carbamate and organophosphate pesticides), vitellogenin-like protein level (Vtg-LP, marker of endocrine disruption caused by the environmental steroids), and ethoxyresorufin-o-deethylase activity (EROD, characteristic for microsomal biotransformation system). Despite criticisms concerning the utility of several markers of specific pollutants in molluscs [32], we included these indices in our study in order to compare their response to that in the indigenous bivalve molluscs [12].…”
Section: Introductionmentioning
confidence: 99%